TIPOLOGI KITAB RIYADLUSH SHALIHIN DALAM KODIFIKASI HADITS - Nur Kholis bin Kurdian (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Hadith is one of the two sources of Islam, both are revelation from Allah Almighty can not be separated, so that the scholars since the time of the companions of the Prophet to the generations after giving great attention to them, they collect the hadith of the Prophet either in the form of writing and memorization or teach it to later generations. Collection of hadiths are then collected into books of hadith with a variety of shades, such as Musnad books, jawami', Sunan, mukhtalif al-hadith, ajza' , Mustadrak, mu‟jam, mustakhraj, al-jam'u baina alshahihain, al-maudlu'at, al-ahkam, gharib al-hadith, al-targhib wa altarhib, athraf, takhrij, zawaid and others. This paper discusses the book of Riyadh al-Saliheen which is one hadith books are well known in the Islamic world. The author will discuss it into 2 parts. First: a discussion of hadith book style category of Riyadh al-Saliheen. Second, the discussion time appeared shades hadith books of Riyadh al-Saliheen. This paper discusses some of the issues related to the typology and the codification of hadith and scope of Riyadh al-Saliheen book. The authors claimed that the book of Riyadh al-Saliheen is one of the books of hadith al-targhib wa al-tarhib the best , and the emergence of this hadith book style since the second century hijriyah as thematic work, then the peak is in the sixth century to the ninth century.